Anecdotes from life - O. Yu (Law Text Culture, 1995)
he is going back he has already bought a ticket why in such a haste because he is sick, of and in australia his girl has left him a catholic girl whose parents object to her marrying a non-catholic oh the most beautiful girl in his factory in his work group another man also loves her a yugoslavian but she prefers him you have seen him you know what a fine young man he is having obtained a b.a. in philosophy taller than most of the chinese but her parents just don't allow her to marry him such stubborn people so backward in outlook so unenlightened in thinking the girl has to quit the factory to quit him but even in china no parents can stop their girls marrying the men they want to marry absolutely none can do that it's incredible that such things can have happened in a country that claims itself progressive and free i suppose what is at work is damned white supremacy